Abortion Laws and Women's Health - Damian Clarke; Hanna Mühlrad (Institute of Labor Economics (IZA), 2018)
We examine the impact of progressive and regressive abortion legislation on women's health and survival in Mexico. Following a 2007 reform in the Federal District of Mexico which decriminalised and subsidised early-term elective abortion, multiple other Mexican states increased sanctions on illegal abortion. We observe that the original progressive policy resulted in a sharp decline in maternal morbidity, particularly maternal morbidity due to haemorrhage early in pregnancy. We observe small or null impacts on women's health from increasing sanctions on illegal abortion. We find some evidence to suggest that these impacts were also observed when considering maternal mortality, though effects are less precisely estimated.
Keywords: I18; J13; K38; H75; 330; abortion; maternal morbidity; maternal mortality; political economy; legislative reform